Toxicity of Nanocomplexes Containing Gadolinium Orthovanadate Nanoparticles and Cholesterol - Goltsev, Anatoliy; Babenko, Natalia; Gaevska, Yuliіa; Bondarovych, Mykola; Dubrava, Tetiana; Ostankova, Lyudmila; Volkova, Nataliia; Klochkov, Vladimir (Biological Trace Element Research. 2022, Jan 13., 2022)
Previous studies have shown the ability of nanocomplexes (NCs), which consist of nanoparticles (NPs) of orthovanadates of rare earth metals (GdYVO4:Eu3+) and cholesterol, to inhibit the growth of Ehrlich’s ascites carcinoma (EAC). However, the biosafety of these NCs remains unclear. Our objective was to investigate the acute and subchronic toxicity of NCs. NCs were administered to BALB/c mice in NPs concentration of 5.9; 29.5; 59.1; and 118.2 mg/kg. Acute toxicity was induced by a single administration of NCs, subchronic-by repeated daily administration of NCs for 14 days. On day 15 and on day 31 for acute and subchronic toxicity, respectively, the percentage of animal survival, body weight, condition of visceral organs, and activities of γ-glutamyl transferase (GGT) and glucose-6-phosphate dehydrogenase (G-6-PDH) were determined. It was found that administration of NCs in the concentration of 5.9 mg/kg and 29.5 mg/kg of NPs did not influence on survival of animals or have a negative impact on their performance status, morphological and quantitative characteristics of visceral organs, and activities of the GGT and G-6-PDH in the liver. For acute toxicity, the semi-lethal dose (LD50) of nanocomplexes was determined (118.2 mg/kg of NPs). As to subchronic toxicity, it was found that repeated (for 14 days) administration of NCs containing 59.1 mg/kg of NPs decrease survival of animals to 50%. The coefficient of accumulation (Cacum = 7) indicates the low accumulative ability of NCs upon long-term use. Thus, from the LD50 and accumulation coefficient, NCs can be referred to as low-toxic substances and used in conditionally therapeutic doses in oncological practice to develop nanostructured formulations of drugs.
Goltsev A, Babenko N, Gaevska Yu, Bondarovych M, Dubrava T, Ostankova L, Volkova N, Klochkov V. Toxicity of Nanocomplexes Containing Gadolinium Orthovanadate Nanoparticles and Cholesterol. Biological Trace Element Research. 2022, Jan 13. https://doi.org/10.1007/s12011-021-03019-z
Keywords: Acute toxicity; Subchronic toxicity; Nanocomplexes; Orthovanadate